A Study on Relationship between Carrying Schoolbags and the Prevalence of Neck and Back Pain among 7 - 9 Year Old Students - Kabilmiharbi N.; Santhirasegaram T. (EDP Sciences, 2023)
Education; Health; Statistical methods; Back pain; Body part discomforts; Malaysia; Maximum allowable loads; Musculoskeletal disorders; School students; Students